ASSESSMENT OF KEEPING QUALITY AND MICROBIAL LOAD OF Staphylococcus aureus IN CATTLE MILK, PROCESSING FACILITIES, AND ENVIRONMENT IN NORTHERN OYO STATE, NIGERIA - Ghali-Mohammed, Ibraheem; Azeez, Aminullah A.; Akeem, Ahmed Olayiwola; Adetona, Mutiat Adenike; Adeyemo, Ismail A.; Olawoye, Oluwadamilola Christiana; Alhaji, Nma Bida; Odetokun, Ismail A. (FUDMA Journal of Sciences, 2025)
Milk is a vital nutritional resource but is highly perishable and prone to contamination by pathogens like Staphylococcus aureus, posing significant public health risks. In Northern Oyo State, where dairy production is predominantly traditional, poor hygiene practices and limited sanitation infrastructure exacerbate these risks. This study addresses gaps in understanding the keeping quality and microbial contamination of raw milk in the region, providing data to improve safety standards. A cross-sectional study was conducted from August 2023 to January 2024, collecting 1,200 samples from five Local Government Areas (LGAs). These samples included raw milk, swabs from milk handlers, and environmental sources. The keeping quality of milk was assessed using the methylene blue reduction test (MBRT) and total bacterial count (TBC) was used to determine microbial load. S. aureus was isolated using standard culture methods. Results revealed that 81.4% of raw milk samples demonstrated “very good” keeping quality, while 4.8% were categorized as “very bad.” TBCs across all samples exceeded international safety standards, indicating significant microbial contamination. The prevalence of S. aureus was 2.7%, with most isolates originating from milk handlers, emphasizing poor hygiene practices as a critical factor. These findings highlighted the urgent need for improved sanitation, handler training, and proper milk storage protocols to enhance dairy safety and protect public health. This study provides foundational data to guide interventions aimed at reducing microbial contamination in Nigeria’s dairy sector.